The Relationship Between Maternal Nutritional Status and the Incidence of Stunting: A Meta-Analysis - Putri, Tyas Aisyah; Salsabilla, Dinda Anindita; Muthi’ah, Tis’a Salma; Vergawita, Tania; Komisah, Komisah (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Stunting remains a major global health concern, contributing to child mortality and long-term developmental consequences. Maternal nutritional status during pregnancy plays a crucial role in determining child growth outcomes. Understanding this relationship is essential for developing effective nutritional interventions to prevent stunting. Subjects and Method: This study is a systematic review and meta-analysis examining the association between maternal nutritional status and stunting in children under five. Relevant studies published between January 2019 and July 2024 were retrieved from PubMed, Science Direct, Google Scholar, and BMJ. Data from nine studies across Asia and Africa were analyzed using Review Manager (RevMan) 5.3. Results: The analysis revealed that underweight mothers had a 1.22 times higher risk of having stunted children, while overweight mothers had a 1.02 times higher risk. Both findings were statistically significant (p<0.001). These results highlight the critical influence of maternal nutritional status on child growth and the increased risk of stunting in both underweight and overweight mothers. Conclusion: Maternal nutrition during pregnancy plays a vital role in preventing stunting among children under five. Targeted nutritional interventions for underweight and overweight mothers are essential to improve maternal and child health outcomes. Strengthening maternal nutrition programs can significantly contribute to reducing global stunting rates.